-
Notifications
You must be signed in to change notification settings - Fork 0
/
Copy pathFib.lean
172 lines (142 loc) · 4.67 KB
/
Fib.lean
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
variable {α : Type u} (f : α → α) (x : α)
def iterate₁ : Nat → α
| 0 => x
| n + 1 => f (iterate₁ n)
theorem iterate₁_succ : ∀ n, iterate₁ f x (n + 1) = iterate₁ f (f x) n
| 0 => rfl
| n + 1 => congrArg f (iterate₁_succ n)
def iterate₂ (x : α) : Nat → α
| 0 => x
| n + 1 => iterate₂ (f x) n
theorem iterate₂_succ x : ∀ n, iterate₂ f x (n + 1) = f (iterate₂ f x n)
| 0 => rfl
| n + 1 => iterate₂_succ (f x) n
theorem iterate₁_eq_iterate₂ x : ∀ n, iterate₁ f x n = iterate₂ f x n
| 0 => rfl
| n + 1 => (iterate₁_succ f x n).trans (iterate₁_eq_iterate₂ (f x) n)
theorem iterate₂_eq_iterate₁ : ∀ n, iterate₂ f x n = iterate₁ f x n
| 0 => rfl
| n + 1 => (iterate₂_succ f x n).trans (congrArg f (iterate₂_eq_iterate₁ n))
def iterate (n : Nat) : α :=
Std.Range.forIn (m := Id) [:n] x λ _ x => .yield (f x)
theorem iterate_eq_iterate₂ : iterate f x n = iterate₂ f x n := by
show Std.Range.forIn.loop _ _ _ (n + 0) .. = _
generalize 0 = i
induction n generalizing x i with
| zero => apply ite_self
| succ fuel ih =>
have : ¬i ≥ fuel.succ + i :=
Nat.add_comm _ i ▸ (Nat.not_succ_le_self _ <| Nat.le_trans · <| Nat.le_add_right i _)
simp! [this]
rw [Nat.succ_add]
apply ih
theorem forInRange {p : Nat → α → Prop} (px : p 0 x) (pf : ∀ n x, p n x → p (n + 1) (f x)) n : p n (iterate f x n) := by
rw [iterate_eq_iterate₂, iterate₂_eq_iterate₁]
induction n with
| zero => exact px
| succ n ih => exact pf n _ ih
def fib : Nat → Nat
| 0 => 0
| 1 => 1
| n + 2 => fib (n + 1) + fib n
def fib' (n : Nat) : Nat :=
(h n).fst
where h
| 0 => (0, 1)
| n + 1 => let (a, b) := h n; (b, b + a)
theorem fib'_eq_fib n : fib' n = fib n :=
congrArg Prod.fst (h n)
where h : ∀ n, fib'.h n = (fib n, fib (n + 1))
| 0 => rfl
| n + 1 => by rw [fib'.h, h n]; rfl
def fib'' (n : Nat) : Nat :=
h n (0, 1)
where h
| 0, (a, _) => a
| n + 1, (a, b) => h n (b, b + a)
theorem fib''_eq_fib n : fib'' n = fib n :=
h 0 n |>.trans <| congrArg fib <| Nat.zero_add n
where h m : ∀ n, fib''.h n (fib m, fib (m + 1)) = fib (m + n)
| 0 => rfl
| n + 1 => Nat.add_right_comm m n 1 ▸ h (m + 1) n
def ifib (n : Nat) : Nat := Id.run do
let mut (a, b) := (0, 1)
for _ in [:n] do
(a, b) := (b, b + a)
return a
theorem ifib_eq_fib n : ifib n = fib n := by
apply congrArg (a₂ := ⟨fib n, fib (n + 1)⟩) MProd.fst
apply forInRange (p := λ n ab => ab = MProd.mk (fib n) (fib (n + 1)))
. rfl
. intro _ _ ih
cases ih
rfl
variable (f : Nat → α → α) (x : α)
def iterate₁' : Nat → α
| 0 => x
| n + 1 => f n (iterate₁' n)
def iterate₂' : Nat → α :=
h x 0
where h x i
| 0 => x
| n + 1 => h (f i x) (i + 1) n
theorem iterate₂'_eq_iterate₁' : ∀ n, iterate₂' f x n = iterate₁' f x n
| 0 => rfl
| n + 1 => .trans (h x 0 n) (congrArg (f n) <| iterate₂'_eq_iterate₁' n)
where h x i : ∀ n, iterate₂'.h f x i (n + 1) = f (n + i) (iterate₂'.h f x i n)
| 0 => i.zero_add.symm ▸ rfl
| n + 1 => n.succ_add i ▸ h (f i x) (i + 1) n
def iterate' (n : Nat) : α :=
Std.Range.forIn (m := Id) [:n] x λ i x => .yield (f i x)
theorem iterate'_eq_iterate₂' : iterate' f x n = iterate₂' f x n := by
show Std.Range.forIn.loop _ _ _ (n + 0) .. = iterate₂'.h ..
generalize 0 = i
induction n generalizing x i with
| zero => apply ite_self
| succ fuel ih =>
have : ¬i ≥ fuel.succ + i :=
Nat.add_comm _ i ▸ (Nat.not_succ_le_self _ <| Nat.le_trans · <| Nat.le_add_right i _)
simp! [this]
rw [Nat.succ_add]
apply ih
theorem forInRange' {p : Nat → α → Prop} (px : p 0 x) (pf : ∀ n x, p n x → p (n + 1) (f n x)) n : p n (iterate' f x n) := by
rw [iterate'_eq_iterate₂', iterate₂'_eq_iterate₁']
induction n with
| zero => exact px
| succ n ih => exact pf n _ ih
def fac : Nat → Nat
| 0 => 1
| n + 1 => fac n * (n + 1)
def fac' : Nat → Nat :=
h 1
where h a
| 0 => a
| n + 1 => h (a * (n + 1)) n
theorem fac'_eq_fac n : fac' n = fac n :=
Nat.mul_one (fac n) ▸ h 1 n
where h a : ∀ n, fac'.h a n = fac n * a
| 0 => Nat.one_mul a |>.symm
| n + 1 => h (a * (n + 1)) n |>.trans <| Nat.mul_assoc _ _ a ▸ Nat.mul_comm _ a ▸ rfl
def ifac (n : Nat) : Nat := Id.run do
let mut a := 1
for i in [:n] do
a := a * (i + 1)
return a
theorem ifac_eq_fac n : ifac n = fac n := by
apply forInRange' (p := λ n a => a = fac n)
. rfl
. intro _ _ ih
cases ih
rfl
def fac'' : Nat → Nat :=
h 1 1
where h a i
| 0 => a
| n + 1 => h (a * i) (i + 1) n
partial
def fac''' (n : Nat) : Nat :=
h 1 1
where h a i :=
if i < n
then h (a * (i + 1)) (i + 1)
else a